Adaptação do índice de massa corporal humano para cães - Müller, Daniel Curvello de Mendonça (2007)
The index of corporal mass (ICM) is broadlly used to measure the corporal mass of adults. A high fat index is related to heart and circulation problems, infertility, diabetes, arthritis, difficulty to move around or breathe and problems with cicatrization. Even though there are several studies about these problems, there is no specific method to evaluate weight excess in dogs objectively and precisely. The purpose of this research was to determine an index of corporal mass for dogs based on the existing IMC for human beings. Two hundred and forty six animals of no specific breed and different body conditions were analysed. They were not only measured and weighed, but also evaluated by two distinct veterinarians based on real subjective patterns, which can determine the corporal score. These procedures enabled the acknowledgement of the attained index. The conclusion was that IMCC between 11,8 and 15 kg/m² represent the ideal pattern for dogs of average size that weigh between 10 and 25 kilos.